Pink Technology: Mediamaking Gear for Girls. - Kearney, Mary Celeste (Camera Obscura, 2010)
The article focuses on the feminization of software products since U.S. sketch comedy "Saturday Night Live" presented its fictional commercial "Chess for Girls" in December 1997. Software developers reportedly create girl-friendly software as a marketing strategy to usher girls to appreciating computing as a vital skill and computer technology as important to daily lives of people. Heidi Dangelmaier, a former feminized games advocate, suggests that software developers should make female games without applying pretty and romantic themes.